The relationship between vitamin A and myopia: A population-based study - Yeo Jin Lee; Donghyun Jee (PLoS ONE, 2025)
Purpose We sought to evaluate the relationship between blood vitamin A levels and myopia in adults aged ≥20 years in Korea. Methods We collected data of 15,899 participants aged ≥20 years from the Korean National Health and Nutrition Examination Survey. Participants underwent refraction tests to identify myopia and high myopia, and their blood pressure and obesity levels were measured. Blood tests were conducted to assess vitamin A, fasting blood glucose, triglyceride, and total cholesterol levels. Blood vitamin A levels were classified into quartiles. Results After adjusting for confounding variables like age, sex, income, education, hypertension, diabetes, and obesity, the odds ratio (OR) of blood vitamin A in the second quartile for myopia was 0.66, while the OR in the fourth quartile was 0.74 (P for trend < 0.001). Among women, the ORs for myopia in the second and third quartiles of blood vitamin A levels were 0.48 (95% confidence interval [CI], 0.35–0.66) and 0.67 (95% CI, 0.49–0.90), respectively (P for trend < 0.001). In men, the ORs for high myopia in the second, third, and fourth quartiles of blood vitamin A levels were 0.05 (95% CI, 0.004–0.58), 0.15 (95% CI, 0.024–0.91), and 0.05 (95% CI, 0.008–0.364), respectively (P for trend < 0.001). Conclusion An inverse relationship was observed between higher blood vitamin A levels and the prevalence of myopia. Notably, higher blood vitamin A levels were associated with a lower prevalence of high myopia in men and a lower prevalence of myopia in women.